(untitled) (The International Journal for Scientific Research, 2023)
The maritime industry relies heavily on efficient and effective ship lifting mechanisms for vessel maintenance, repair, and construction. This abstract provides a concise overview of a comprehensive comparison between two prominent ship lifting technologies: Syncrolift and Floating Dry Dock. Syncrolift systems utilize a platform with synchronized lifting mechanisms, while Floating Dry Docks submerge to lift vessels. This comparative analysis delves into various aspects, including operational capabilities, cost-effectiveness, and adaptability to different vessel types. By examining the strengths and limitations of each technology, this study aims to provide valuable insights for maritime stakeholders, shipyards, and naval professionals seeking to optimize their ship lifting processes, enhance operational efficiency, and make informed decisions in the dynamic world of maritime operations. The findings presented herein contribute to a better understanding of these vital technologies and their role in shaping the future of ship maintenance and construction.